KRITIK ATAS PENANGANAN KONFLIK AGRARIA DI INDONESIA - Lilis Mulyani (BHUMI: Jurnal Agraria dan Pertanahan, 2014)
The occurance of agrarian conflict in Indonesia, which are increasing in term of numbers and intensity, showed thatthere is a chronic and systemic problem in Indonesia’s agrarian resource management. This article is re-written based on aresearch conducted through desk research, workshops and series of Focus Groups Discussions to understand the roots andmechanisms of agrarian conflict resolution in some institutions. Among the results are that the increased numbers of newconflicts, and the long-recurrent conflict indicates that the roots of agrarian conflict has not been resolved yet. Meanwhile, thelocal, national and global dynamics have shown a phenomena that potentially leads to other agrarian conflicts. Pressures fromthese dynamics certainly need to be responded by adequate measures and efforts.Keywords: agrarian conflict, conflict resolution